Comparing aerosol concentrations and particle size distributions generated by singing, speaking and breathing. Issue 6 (21st April 2021) - Gregson, Florence K. A.; Watson, Natalie A.; Orton, Christopher M.; Haddrell, Allen E.; McCarthy, Lauren P.; Finnie, Thomas J. R.; Gent, Nick; Donaldson, Gavin. C.; Shah, Pallav L.; Calder, James D.; Bzdek, Bryan R.; Costello, Declan; et al.
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has resulted in an unprecedented shutdown in social and economic activity, with the cultural sector particularly severely affected. Restrictions on musical performances have arisen from a perception that there is a significantly higher risk of aerosol production from singing than speaking, based upon high-profile examples of clusters of COVID-19 following choral rehearsals. However, comparing aerosol generation from different types of vocalization, including singing, across a range of volumes is a rapidly evolving area of research. Here, we measured aerosols from singing, speaking and breathing from a large cohort of 25 professional singers in a range of musical genres in a zero-background environment, allowing unequivocal attribution of aerosol production to specific vocalizations. We do not assess the relative volumes at which people speak and sing. However, both showed steep increases in mass concentration with increase in loudness (spanning a factor of 20–30 across the dynamic range measured, p < 0.001). At the quietest volume (50 to 60 dBA), neither singing ( p = 0.19) nor speaking ( p = 0.20) were significantly different to breathing. At the loudest volume (90 to 100 dBA), a statistically significant difference ( p < 0.001) was observed between singing and speaking, but with singing only generating a factor of between 1.5 and 3.4 more aerosol mass. Guidelines for musical performances should be based on the loudness and duration of the vocalization, the number of participants and the environment in which the activity occurs, rather than the type of vocalization. Mitigations such as the use of amplification and increased attention to ventilation should be employed where practicable. Copyright © 2021 American Association for Aerosol Research